A PCR-mediated method for discrimination of Klebsiella oxytoca between closely related bacteria in environmental and clinical specimens - Kovtunovych, G.L.; Lytvynenko, T.L.; Negrutska, V.V.; Lar, O.V.; Koltukova, N.V; Kozyrovska, N.O. (Біополімери і клітина, 2003)
A specific detection method was developed to discriminate Klebsiella oxytoca between other species of the genus Klebsiella on the basis of PCR amplification of the unique DNA sequences within the polygalacturonase-encoding (pehX) gene. Four primers have been designed for performing PCRs gaining amplicons of 282, 344, 451 and 513 bp. The specificity of the test was verified by the lack of PCR products in case of related K. pneumoniae, K. planticola, and polygalacturonate-degrading species of the genus Erwinia. The PCR-mediated test gives a rapid answer, concerning the presence of K. oxytoca in a sample, or in differentiating this bacterium from other species, such as K. pneumoniae, with which they can be confused. The diagnostic test can be used in ecological monitoring of K. oxytoca as well as in medical laboratories.